TMEM52B-derived peptides inhibit generation of soluble E-cadherin and EGFR activity to suppress colon cancer growth and early metastasis - Yunhee Lee; Dongjoon Ko; Junghwa Yoon; Semi Kim (Journal of Translational Medicine, 2025)
Abstract Background Transmembrane protein 52B (TMEM52B) is a novel gene expressed widely in various normal human tissues; however, the biological function of TMEM52B in cancer remains largely unknown. Previously, we demonstrated that TMEM52B is a novel modulator of E-cadherin and EGFR activity, and that it has tumor suppressor-like activity using both experimental and clinical analyses. Here, we hypothesized that the extracellular domain (ECD) of TMEM52B may exert tumor-suppressing activity. Methods We designed and evaluated the therapeutic potential of TMEM52B ECD-derived peptides in vitro and in vivo. The molecular mechanisms underlying the anti-cancer activity of the peptides were explored. Results TMEM52B ECD-derived peptides reduced cancer cell survival, invasion, and anchorage-independent growth, which was accompanied by decreased phosphorylation of ERK1/2 and AKT. The peptides maintained intact E-cadherin at organized cell–cell junctions, leading to reduced β-catenin activity. They also inhibited generation of soluble E-cadherin and activation of EGFR by binding directly to the E-cadherin ECD and interfering with the interaction between soluble E-cadherin and EGFR. Peptides fused to the Fc domain of human IgG1 efficiently inhibited tumor growth in a colon cancer xenograft model and reduced survival of circulating tumor cells in an early metastasis model. Conclusions These results strongly suggest that TMEM52B ECD-derived peptides could provide a platform for the development of novel anti-cancer therapeutics and furnish a useful tool for exploring the function of TMEM52B in modulating the interplay between E-cadherin and EGFR.